HUMANISME DALAM PENERAPAN SISTEM PEMBELAJARAN JARAK JAUH PADA MASA PANDEMI COVID-19 PADA SEKOLAH LUAR BIASA NEGERI (SLBN) - Mutfi Zhulian; Iin Kandedes (Pusat Studi Gender dan Anak (PSGA), Universitas Islam Negeri Syarif Hidayatullah, 2021)
Abstract. Research conducted at SLB-C SLBN 01 Jakarta for grade 6.1-C This primary school aims to find out How is the process of implementing a distance learning Islamic Religious Education for class 6.1-C mentally retarded students during Covid-19 pandemic at SLBN 01 Jakarta and What are the supporting factors and inhibiting factors in the process of implementing a distance learning Islamic Religious Education for class 6.1-C mentally retarded students during Covid-19 pandemic at SLBN 01 Jakarta.The research method using a qualitative approach with a case study research. This research also using the descriptive method. The results of distance learning research in Islamic Religious Education for mentally retarded students during covid-19 period at SLBN 01 Jakarta show that learning for mental retardation is adjusted to the abilities of students, such as simplifying the material (downgrade) if the PAI material is too difficult, Avoiding the delivery of PAI material abstractly, theoretically, and verbally, Delivery of PAI material in a contextual, practical, easy, visual, gradual, continuous and repetitive manner, Optimizing affective and psychomotor potentials rather than cognitive, Individual learning approach, Using media and methods following the needs of students. The learning support factors that the researchers sows that: there was internet quota assistance provided by schools for teachers and students, there is teacher training, patience and patience of teachers and parents in teaching and assisting children in learning, the school makes a home visit program. Meanwhile, the inhibiting factors include: the teacher independently searches for teaching materials for students, lack of motivation and awareness of students, unstable internet connection, some students do not have cellphones, lack of understanding of the parents about the material being taught, students' low understanding ability. Abstrak. Penelitian yang dilakukan di SLB-C SLBN 01 Jakarta jenjang kelas 6.1-C Sekolah dasar ini bertujuan untuk mengetahui Bagaimana proses pelaksanaan pembelajaran jarak jauh Pendidikan Agama Islam bagi siswa tunagrahita pada masa pandemi covid-19 kelas 6.1-C di SLBN 01 Jakarta dan Apa saja faktor pendukung dan faktor penghambat dalam proses pelaksanaan pembelajaran jarak jauh Pendidikan Agama Islam bagi siswa tunagrahita pada masa pandemi covid-19 kelas 6.1-C di SLBN 01 Jakarta. Adapun metode penelitian yang digunakan dalam penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Penelitian ini juga menggunakan metode deskriptif. Hasil penelitian pembelajaran jarak jauh dalam Pendidikan Agama Islam bagi siswa tunagrahita pada masa covid-19 di SLBN 01 Jakarta menunjukkan bahwa pembelajaran untuk tunagrahita disesuaikan dengan kemampuan peseta didik, seperti Menyederhanakan materi (downgrade) bila materi PAI yang terlalu sulit, Menghindari penyampaian materi PAI secara abstrak, teoristis, dan verbal, Penyampaian materi PAI secara kontektual, praktis, mudah, visual, bertahap, berkesinambungan dan berulang-ulang, Mengoptimalkan potensi afektif dan psikomotorik dari pada kognitif, Pendekatan pembelajaran individual, Menggunakan media dan metode yang sesuai dengan kebutuhan peserta didik. Adapun faktor pendukung pembelajaran yang peneliti temukan menunjukkan bahwa: adanya bantuan kuota internet yang diberikan oleh sekolah untuk guru dan siswa, adanya pelatihan guru, sikap sabar dan ketelatenan guru dan orang tua dalam mengajar dan mendampingi anak belajar, sekolah membuat program home visit. Sedangkan untuk faktor penghambat meliputi: guru mencari secara mandiri bahan ajar untuk siswa, kurangnya motivasi dan kesadaran dari diri siswa, koneksi internet yang tidak stabil, ada beberapa siswa yang tidak memegang handphone, kurangnya pemahaman orang tua tentang materi yang diajarkan, kemampuan pemahaman yang rendah pada diri siswa.